ANALISIS YURIDIS KESADARAN HUKUM PADA REMAJA DALAM KETAATAN LALU LINTAS SESUAI UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN - RAHMAN, YAHYA IBADU (Dinamika Hukum, 2018)
The result of research of legal awareness study on adolescent in the appropriate traffic obedience, that is still less, this is proven by adolescent do not execute existing traffic rules. This is evidenced still many occurrences of violations of the law of traffic conducted by adolescents. In addition to violations committed by students is a violation of red lights, no SIM, and do not use the completeness of driving include: not using the rearview mirror, not using a helmet, and non-standard vehicle conditions. Many students who do not have a SIM because they are not old enough, do not have the cost, and do not know the information how the procedure to create a driver's license that already has a SIM. The factors that inhibit the increase of legal awareness in adolescents in traffic compliance in accordance with the law number 22 of 2009, namely: The Use of Vehicles by teenagers They average not enough age in taking the Driver's License (SIM), sociological knowledge structure of society, namely the thinking that always underestimate things, public knowledge about the law number 22 of 2009 is still very minimal. Steps that can be done so that our teenagers understand the importance of traffic awareness that is, it is necessary to socialize that children who do not have a driver's license should not bring a motor vehicle considering their psychological and mental conditions are not stable to deal with events on the streets and not skilled in running his vehicle. Keywords: Legal Awareness, Youth, Traffic Adherence